Recognition of Hijaiyah Letter Patterns Using The Bidirectional Associative Memory Method - Nanda Jarti; Sestri Novia Rizki (Indonesian Journal of Artificial Intelligence and Data Mining, 2024)
Artificial Intelligence has a very broad scope so it can solve very complex problems. Hijaiyah letter pattern recognition using the Bidirectional Associative Memory (BAM) method has the ability to detect maximum results for the blind who are learning to recognize hijaiyah letters in producing information using a bipolar system. The problem in this research is the difficulty for blind people in recognizing hijaiyah letters and patterns, so this research was designed to help blind people learn hijaiyah letters so that they can easily understand the patterns and types of letters using the 3x3 order matrix concept. In the BAM has the advantage of layers that are interconnected between one layer and another layer so that they can be connected from the input layer to the output layer. This research will produce a Hijaiyah letter recognition pattern using the 3x3 Matrix system to design a system for identifying Hijaiyah letter patterns. From the results of the tests that have been carried out, there are 5 Hijaiyah letter patterns, namely ا, ث, ج, ذ and ش which are processed by pattern recognition with a value of 1. [1.1] [1,-13],[-1,1][3,-11 ],[1,-1] [-9,-17],] [-1,1][ [13,9], [-1,1][-13,13]. Of the 5 Hijaiyah letter patterns, only 2 letter patterns were able to be recognized by the system, namely the letters ذ and ش, and 3 patterns were not able to be recognized by the system. Thus it can be concluded that not all patterns using the BAM method are able to recognize patterns precisely and correctly.